3.2.2 Traceable Engineering of Fault‐Tolerant SoSs. Issue 1 (July 2014) - Andrews, Zoe; Ingram, Claire; Payne, Richard; Romanovsky, Alexander; Holt, Jon; Perry, Simon
Abstract Systems of systems (SoSs) are characterised by a challenging combination of continuous evolution, emergent behaviour and distributed, autonomous and independent constituents. The development of SoSs that can tolerate faults and harmful events is hampered by these and other complexities. Currently there is little in the way of methods or tools to help SoS developers to design fault‐tolerant SoSs. In this paper we present a structured approach for capturing requirements for a fault‐tolerant SoS and a fault modelling architectural framework (FMAF) that supports disciplined and reusable development of fault‐tolerant architectures. We also provide a traceable mapping of the fault‐tolerant requirements into SoS architectural designs. Finally we apply our techniques to a real‐world SoS case study.